Renal function ascertainment rate of patients at community pharmacies in Japan: a national survey - Yuki Kondo; Yoshiaki Shikamura; Manabu Suzuki; Masao Takahashi; Eiji Kawakami; Hajime Hashiba; Choichiro Miyazaki (Renal Replacement Therapy)
Abstract Background Chronic kidney disease is a major healthcare problem worldwide, including in Japan, and renal dysfunction is a significant risk factor for adverse drug reactions. To ensure the proper use of medicine in patients with chronic kidney disease, community pharmacists must ascertain their renal function. However, it is not known how often this happens in Japan. We conducted a study to clarify this situation and identify associated issues in Japanese community pharmacies. Methods We analyzed the results of a nationwide survey of community pharmacies conducted by the Japan Pharmaceutical Association. The survey included questions on background information about patients who used community pharmacies, and whether pharmacists were able to confirm laboratory values. We calculated how often renal function was ascertained in community pharmacies on the basis of these results. The renal function ascertainment rate in community pharmacies was analyzed by patient background and region. Results A total of 416,782 participants were included in the analysis, and 5.5% of these had their renal function ascertained at the community pharmacy. The rate of ascertainment of renal function remained low even in older people, patients with cancer, and rheumatoid arthritis, although renal function is an important issue for these groups. It was also generally low in eastern Japan. Conclusions The rate of ascertainment of renal function in Japanese community pharmacies is low, even among older people, patients with cancer, and people with rheumatoid arthritis, in whom the ascertainment of renal function is especially important. Nationwide measures, including the correction of regional differences, are needed to implement safe pharmacotherapy in patients with renal dysfunction.